Welding training to enhance welding skills for youth in Cilegon City - Yeni Muriani Zulaida; Suryana Suryana; Agus Pramono; Andinnie Juniarsih; Indah Uswatun Hasanah (Journal of Community Service in Science and Engineering (JoCSE), 2024)
Cilegon is one of the cities in Banten. The large number of factories in Cilegon City makes this city known as an industrial city. Several industrial activities, ranging from primary to supporting activities, require a lot of labor. The need for labor in Cilegon, especially in the manufacturing sector, is increasing. To increase the competitiveness of local communities in obtaining more excellent employment opportunities, young people of productive age, especially, need to be equipped with skills that support industrial activities. One of these skills is metal welding. To introduce this skill, a welding training program was conducted for young people in Cilegon City. The methods used include lectures, demonstrations, and welding practice. The material provided during the training consists of an introduction to welding equipment, essential steps in the welding process, K3 in the welding industry, and home industry planning in the field of metal welding. This training successfully attracted several young people from Grogol and Purwakarta sub-districts. After this training, they can improve their skills, expand job opportunities, and even become self-employed in welding. Cilegon adalah salah satu kota di Banten. Banyaknya pabrik-pabrik di Kota Cilegon membuat kota ini disebut sebagai kota industri. Beberapa kegiatan industri mulai dari kegiatan utama hingga kegiatan pendukung membutuhkan banyak tenaga kerja. Kebutuhan tenaga kerja di kota Cilegon terutama di bidang manufaktur meningkat. Untuk meningkatkan daya saing masyarakat lokal dalam mendapatkan peluang kerja yang lebih besar, khusus para pemuda usia produktif, perlu dibekali keahlian yang menunjang kegiatan industri tersebut. Salah satu keahlian tersebut adalah pengelasan logam. Dalam rangka mengenalkan keahlian ini maka dilaksanakan kegiatan program pelatihan pengelasan bagi para pemuda di Kota Cilegon. Metode yang digunakan meliputi ceramah, demonstrasi dan praktek pengelasan. Materi yang diberikan selama pelatihan meliputi pengenalan peralatan pengelasan, langkah-langkah dasar proses pengelasan, K3 pada industri pengelasan dan perencanaan industri rumahan di bidang pengelasan logam. Pelatihan ini berhasil menjaring beberapa pemuda dari kecamatan Grogol dan Purwakarta, Diharapkan setelah pelatihan ini dapat meningkatkan keahlian, memperluas peluang kerja bahkan dapat berwiraswasta di bidang pengelasan.